Adaptation of Gamification as a Man-Machine Interface to Franchise Management System - ALTUNEL, YUSUF; GÜNAYDIN, BURAK; KALABALIKOĞLU, FURKAN (Institute of Electrical and Electronics Engineers Inc., 2021)
Current man-machine interfaces are far from fitting human expectations in understanding and transmission of noteworthy signs and hints that are natural ingredients of human communication. There are certain indicators and interaction possibilities that can be passed between the two sides but as a result of complex behavior and dynamic changing conditions of environments they can be lost, or at least might require long and complex processing. Gamification is used to enhance the interaction possibilities providing the visual representation of environmental conditions and critical indicators, as well as providing the ability to send and receive requests using suitable techniques for human such as touches, and finger moves on Unity environment. Franchise Management System is selected as a case study and adapted to maintain the interactions between franchiser and franchisee. © 2021 IEEE.
ISMSIT 2021 - 5th International Symposium on Multidisciplinary Studies and Innovative Technologies, Proceedings
5h International Symposium on Multidisciplinary Studies and Innovative Technologies, ISMSIT 2021, Ankara, 21 October 2021through 23 October 2021.
Keywords: Franchisee; Franchiser; Game; Gamification; Human-computer Interaction; Man-machine Interface